Anti‐TIF‐1γ dermatomyositis: Erythematous eruption with weakness and normal creatine kinase - Lucy Mackie; Nilukshi Wijesuriya; Ashok Iyer (Wiley, 2024)
Abstract We describe a case of a previously well 76‐year‐old woman who presented with 9 months of a generalised pruritic rash alongside fatigue, weight‐loss and a symmetrical weakness of the legs.